2021
DOI: 10.18549/pharmpract.2021.2.2269
|View full text |Cite
|
Sign up to set email alerts
|

The competency of Indonesian pharmacy students in handling a self-medication request for a cough: a simulated patient study

Abstract: Background: Cough is a common symptom for which people frequently present to community pharmacies. Previous articles from developing countries have shown that the provision of self-medication consultation for cough in community pharmacies were suboptimal, with knowledge deficiency being a contributing factor. However, little is known regarding the ability of pharmacy students in handling self-medication consultations in developing countries. Objectives: To measure the competency of Indonesian pharmacy st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This problem may be attributed to the lack of sufficient knowledge about the needed non-pharmacological measures to manage diarrhea and other minor ailments. Similarly, few of the Indonesian pharmacy students mentioned non-pharmacological advice for patients with cough [ 28 ]. Meanwhile, the advice about lifestyle measures was mentioned by nearly all the participated students after they used the application.…”
Section: Discussionmentioning
confidence: 99%
“…This problem may be attributed to the lack of sufficient knowledge about the needed non-pharmacological measures to manage diarrhea and other minor ailments. Similarly, few of the Indonesian pharmacy students mentioned non-pharmacological advice for patients with cough [ 28 ]. Meanwhile, the advice about lifestyle measures was mentioned by nearly all the participated students after they used the application.…”
Section: Discussionmentioning
confidence: 99%
“…The number of pharmacy students who were able to provide appropriate recommendations was higher in this cohort compared with another Indonesian study. 22 Differences in the students' grade level (final year vs third year), the scenario used (analgesic-antipyretic cases vs cough case), and the assessment method (case vignette vs simulated patient) might be factors causing the differences between the two studies. This may indicate that their university teaching and learning processes have equipped them quite well to manage analgesic-antipyretic self-medication cases.…”
Section: No Reason Provided 3 (3%)mentioning
confidence: 99%
“…21 Another study showed that approximately only 55% of 183 third-year BPharm students participating in the research were able to provide appropriate recommendations in the case of cough due to asthma worsening. 22 Furthermore, a study from a faculty of pharmacy in Surabaya found that 71% of 86 apothecary students were able to provide appropriate recommendations in a case of low back pain. 23 While few studies related to the ability of pharmacy students to handle self-medication cases have been conducted, the results were varied.…”
mentioning
confidence: 99%